Expert Sample Consensus (ESAC) for visual re-localization [data] - Brachmann, Eric (Universität, 2020)
Supplementary training data for visual camera re-localization, particularly pre-computed scene coordinates to the MSR 7Scenes dataset and the Standford 12Scenes dataset. We also provide pre-trained models of our method for the 7Scenes, 12Scenes, Dubrovnik and Aachen (day) datasets. For more information, also see the code documentation: https://github.com/vislearn/esac